2016
DOI: 10.4314/ahs.v16i1.31
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in pre-dialysis chronic kidney disease patients in a teaching hospital in Southern Nigeria

Abstract: Background: Malnutrition is a complication in chronic kidney disease (CKD) known to affect quality of life and prognosis although not often diagnosed. It is associated with rapid progression to end stage renal disease (ESRD) and mortality. Early identification and treatment will slow down progression to ESRD and mortality. Objective: To determine the prevalence and pattern of malnutrition in pre-dialysis CKD patients in Southern Nigeria. Methods: One hundred and twenty consecutive pre-dialysis CKD and 40 contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
4
22
2
Order By: Relevance
“…This finding was similar to the Southern Nigeria study which reported that malnutrition was significantly commoner in elderly patients (p=0.047). 20 …”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to the Southern Nigeria study which reported that malnutrition was significantly commoner in elderly patients (p=0.047). 20 …”
Section: Discussionmentioning
confidence: 99%
“…Reduced serum albumin is considered a strong predictor of morbidity and mortality in the CKD population in all stages and, with other clinical parameters, is an indicative of dialysis therapy initiation 19,20 . In addition, hypoalbuminemia may indicate inflammation and depletion of nutritional status 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of MAC values, regardless of body weight and state of hydration and inflammation, may suggest decreased muscle mass. Reduction of lean mass, inflammatory state, and hypoalbuminemia are considered risk factors for cardiovascular disease, increased mortality, and rapid progression of CKD 20 .…”
Section: Discussionmentioning
confidence: 99%
“…47 Malnutrition in turn is associated with reduced quality of life, sleep problems, depression, erythropoietin hypo-responsiveness, immunosuppression, and heart failure exacerbation in patients with ESKD. 47 Malnutrition in itself is already associated with increased all-cause mortality and MACE rates in subjects with CAD. 48 In this specific population of patients after KT, malnutrition is associated with longer transplant hospitalization length of stays, higher all-cause graft loss, and higher mortality.…”
Section: Discussionmentioning
confidence: 99%